Protection for Fashion in Shi’a Jurisprudence - Mohaqeq Damad, Seyyed Mostafa; Rasuli, Hasan (Opción, 2019)
Along with the growth of intellectual property rights, trends and areas asso- ciated with this field have undergone changes. One of the major domains of intellectual property that today has gained a great position and importance in the world, is the concept referring to fashion (Mode) and creations of Beauty and Wear. Although lawyers often scrutinize fashion in the field of literary property rights, and sometimes in the form of industrial property rights, the status of fashion as an important part of intellectual property rights is undeni- able. In Shi’a jurisprudence, there are various views on intellectual property rights, which are generally true in the concept of fashion, too. In general, there are two views in Shi’i jurisprudence on intellectual property and, conse- quently, of fashion. According to the first comment, intellectual property and consequently fashion are lacking in legal terms, and the holy legislator has not provided any protection for fashion. However, the group believes that some rights can be recognized through the terms of legal contracts for intellectual people. On the contrary, the second group, with the full support of fashion, believes that the holy legislator, in general primary rulings, as well as sec- ondary ones such as “La-Zarar” (Prohibition of Detriment) and “La-Haraj” (No Distress), etc., have implicitly supported the thoughts. However, given the growth of the fashion arena, it seems that the second approach is consistent with global developments.